Legionella species colonization of water distribution systems, pools and air conditioning systems in cruise ships and ferries - Gourgoulianis Kostantinos; Kavagias Antonios; Stathakis Nikolaos E; Karanika Maria; Mouchtouri Varvara A; Goutziana Georgia; Kremastinou Jenny; Hadjichristodoulou Christos (BMC, 2008)
Abstract Background Legionnaires' disease continues to be a public health concern in passenger ships. This study was scheduled in order to investigate Legionella spp. colonization of water distribution systems (WDS), recreational pools, and air-conditioning systems on board ferries and cruise ships in an attempt to identify risk factors for Legionella spp. colonization associated with ship water systems and water characteristics. Methods Water systems of 21 ferries and 10 cruise ships including WDS, air conditioning systems and pools were investigated for the presence of Legionella spp. Results The 133 samples collected from the 10 cruise ships WDS, air conditioning systems and pools were negative for Legionella spp. Of the 21 ferries WDS examined, 14 (66.7%) were legionellae-positive. A total of 276 samples were collected from WDS and air conditioning systems. Legionella spp. was isolated from 37.8% of the hot water samples and 17.5% of the cold water samples. Of the total 96 positive isolates, 87 (90.6%) were L. pneumophila. Legionella spp. colonization was positively associated with ship age. The temperature of the hot water samples was negatively associated with colonization of L. pneumophila serogroup (sg) 1 and that of L. pneumophila sg 2 to 14. Increases in pH ≥7.8 and total plate count ≥400 CFU/L, correlated positively with the counts of L. pneumophila sg 2 to 14 and Legionella spp. respectively. Free chlorine of ≥0.2 mg/L inhibited colonization of Legionella spp. Conclusion WDS of ferries can be heavily colonized by Legionella spp. and may present a risk of Legionnaires' disease for passengers and crew members. Guidelines and advising of Legionnaires' disease prevention regarding ferries are needed, in particular for operators and crew members.